Southern Ocean forcing of the North Atlantic at multi-centennial time scales in the Kiel Climate Model - Torge Martin; Wonsun Park; Mojib Latif (Deep Sea Research Part II: Topical Studies in Oceanography, 2015)
Internal multi-centennial variability of open ocean deep convection in the Atlantic sector of the Southern Ocean impacts the strength of the Atlantic Meridional Overturning Circulation (AMOC) in the Kiel Climate Model. The northward extent of Antarctic Bottom Water (AABW) strongly depends on the state of Weddell Sea deep convection. The retreat of AABW results in an enhanced meridional density gradient that drives an increase in the strength and vertical extent of the North Atlantic Deep Water (NADW) cell. This shows, for instance, as a peak in AMOC strength at 30°N about a century after Weddell Sea deep convection has ceased. The stronger southward flow of NADW is compensated by an expansion of the North Atlantic subpolar gyre and an acceleration of the North Atlantic Current, indicating greater deep water formation. Contractions of the North Atlantic subpolar gyre enable warm water anomalies, which evolved in response to deep convection events in the Southern Ocean, to penetrate farther to the north, eventually weakening the AMOC and closing a quasi-centennial cycle. Gyre contractions are accompanied by increases in sea level of up to 20cm/century in some areas of the North Atlantic. In the Southern Ocean itself, the heat loss during the convective regime results in a sea surface height decrease on the order of 10cm/century, with a maximum of 30cm/century in the Weddell Sea. Hence, the impact of the Southern Ocean Centennial Variability (SOCV) on regional as well as North Atlantic sea level is of the same order of magnitude as the rise of global average sea level during the 20th century, which amounts to about 15–20cm. This suggests that internal variability on a centennial time scale cannot be neglected a priori in assessments of 20th and 21st century AMOC and regional sea level change. Deep Sea Research Part II is a green OA journal, publisher's version will be available in 12 - 48 months after the publication on 30 Jan. 2014, post-print available